An institute of state criminal responsibility as an effective international legal mechanism for combating the crime of aggression - Антипенко, В. Ф.; Важна, К. А. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
This article describes the lack of effectiveness of current international legal mechanisms for combatingthe crime of aggression and the need to improve these mechanisms or create new ones. The author bringsarguments in favor of that institute of state criminal responsibility is able to become an effective internationallegal mechanism for combating the crime of aggression and other international crimes.